54.7k views
4 votes
How do I solve for x in the problem 2(3x-2)= 6x-2

2 Answers

2 votes

12x-4=6x-2

-6x -6x

------------------

6x-4=-2

+4 +4

6x 2

----- = ------

6 6

x= ?

In order to find x you need to divide 2 and 6!

Hope this helped!!!

User Tanvir Ahmed
by
4.3k points
3 votes

Answer:

First: You're going to want to factor 2(3x-2). You will get 6x-4. Then you're going to want subtract 6x from both sides which will actually give you "no solution" because there will no longer be an x.

User Roman Bekkiev
by
5.5k points